2017
DOI: 10.1159/000477564
|View full text |Cite
|
Sign up to set email alerts
|

Early Evaluation of the Fetal Heart

Abstract: Evaluation of the fetal heart at 11-13 + 6 weeks of gestation is indicated for women with a family history of congenital heart defects (CHD), a previous child with CDH, or an ultrasound finding associated with cardiac anomalies. The accuracy for early detection of CHD is highly related to the experience of the operator. The 4-chamber view and outflow tracts are the most important planes for identification of an abnormal heart, and can be obtained in the majority of fetuses from 11 weeks of gestation onward. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 108 publications
(98 reference statements)
0
35
0
7
Order By: Relevance
“…We have provided standardized and comprehensive reference values for fetal cardiac morphometric parameters across gestation in a low-risk population. An accurate measurement of heart dimensions might be very useful to identify and monitor cardiac remodeling -change in shape, size, and structure -in response to pressure/volume overload or cardiac toxicity in many conditions, such as CHD [36,37], maternal diabetes [9], twin-to-twin transfusion syndrome [38], FGR [39], conception by ART [7], fetal anemia [40], congenital diaphragmatic hernia [41], or exposure to antiretroviral drugs [8]. A better understanding and follow-up of fetal cardiac adaptations could enable early interventions and minimize long-term cardiovascular consequences [42].…”
Section: Discussionmentioning
confidence: 99%
“…We have provided standardized and comprehensive reference values for fetal cardiac morphometric parameters across gestation in a low-risk population. An accurate measurement of heart dimensions might be very useful to identify and monitor cardiac remodeling -change in shape, size, and structure -in response to pressure/volume overload or cardiac toxicity in many conditions, such as CHD [36,37], maternal diabetes [9], twin-to-twin transfusion syndrome [38], FGR [39], conception by ART [7], fetal anemia [40], congenital diaphragmatic hernia [41], or exposure to antiretroviral drugs [8]. A better understanding and follow-up of fetal cardiac adaptations could enable early interventions and minimize long-term cardiovascular consequences [42].…”
Section: Discussionmentioning
confidence: 99%
“…This period ensures that a full assessment of the developed cardiac anatomy can be performed whilst allowing time for further assessment with echocardiogram, amniocentesis, etc, whilst still previable . Whilst TOF has been detected with obstetric ultrasound earlier than 18‐week gestation, Hernandez‐Andrade et al demonstrated it was unlikely to be detected less than or equal to 14‐week gestation.…”
Section: Resultsmentioning
confidence: 99%
“…El tamizaje del primer trimestre en las semanas 11-14, que comenzó con la evaluación de la TN para la detección de la trisomía 21 y otras aneuploidías, se fue extendiendo para el diagnóstico de varias malformaciones mayores. [19][20][21][22][23][24][25][26] La ecografía de las semanas 11-14 podría jugar un rol importante en la detección de CC por la visualización directa del defecto o por la presencia de marcadores ecográficos que incrementaran el riesgo.…”
Section: ¿Se Puede Evaluar El Corazón Fetal En El Primer Trimestre?unclassified
“…Por ello, algunos autores sugieren la evaluación precoz del corazón fetal mediante el corte de 4 cámaras y los tractos de salida, que, luego de la semana 12, pueden obtenerse en la gran mayoría de los casos. 19 Otros cortes, en cambio, son más difíciles de obtener (Tabla 3). McAuliffe y col., reportaron que, a las 13 + 5 semanas, los arcos aórtico y ductal solo pudieron verse en el 45 % de los casos y las venas pulmonares, en el 16 % de los fetos estudiados.…”
Section: A Visualización Directa De La Cardiopatía Congénitaunclassified
See 1 more Smart Citation